Farmers’ Preferences Selecting Agricultural Consulting Services - Vilma Tamuliene; Asta Raupeliene; Egle Kazlauskiene (Montenegrin Journal of Economics)
The Lithuanian farmers face with a huge need for information and counselling services to increase the competitiveness of farms and to increase farmers' ability to use the EU and Lithuanian government support funds for them. Farmers need to meet their needs of specific consulting services provided by various organizations and individual consultants in Lithuania. This raises the question: what are the most important factors for farmers choosing consulting services. Those are important for implications for consulting service business strategy and regulatory policies. Hypothesis - the most important factors of farmers’ selecting agricultural consulting services are the counselling content, the counselling technique and the length of counselling. The aim of the paper - to identify and investigate the factors influencing farmers’ preferences selecting agricultural consulting services. The analysis of these issues was a basis for empirical research in Lithuania. For the research completion, the methods of questionnaire survey were applied. The results of the study showed that the most significant factors forming farmers' preferences selecting agricultural consulting services are consulting content and length of consulting. The regressive analysis enabled the research in causality of connections and revealed that there is present linear and statistically strong or very strong impact among these variables. Also there are present direct and meaningful impacts: between counselling content and farmers’ age, between length of counselling and farmers’ the level of education and the type of farming..